Feedback and guiding questions as tools for reflective writing: a comparative study among undergraduate medical students in India - Shruti Prabhat Hedge; Vijay Kautilya Dayanidhi (BMC Medical Education)
Abstract Introduction Reflective writing helps foster clinical reasoning, and professional development in medical students. This study attempts to compare the effectiveness of two interventions—Structured guiding questions and individualized feedback for enhancing reflective writing skills among undergraduate medical students in India. Methodology A quasi-experimental, semi-qualitative study was conducted among 30 third-year MBBS students of Shri Sathya Sai Medical College and Research Institute, Chennai. Participants were randomly allocated into two groups of 15 each. Group A used a structured guiding question, while Group B received individual feedback on the reflections from trained faculty. All students wrote five reflections pre- and post-intervention on their clinical experiences in Ophthalmology. The fifth reflections were assessed by three experts using a validated rubric. Pre- and post-intervention scores were compared using the Wilcoxon Signed Rank Test, and Mann-Whitney U Test was used for intergroup comparison. Semi-quantitative feedback and open-ended responses were used for student perception. Results Both interventions led to statistically significant improvements in reflective writing (p < 0.01). Guiding question Group’s average score improved from 1.33 to 2.27, and Feedback Groups from 1.13 to 2.00. No significant difference was observed between the post-intervention scores of both groups (p > 0.05). Feedback and guiding questions, both were perceived to be useful, as guiding questions helped structure the reflection, and feedback supported emotional connection. Conclusion Both tools were found to be effective to improve the quality of reflections. Integrating guiding questions and feedback can prove to be a better strategy to support Competency Based Medical Education. Trial registration ‘Clinical trial number not applicable.’